PENGARUH DISIPLIN KERJA, KOMITMEN ORGANISASI DAN KEMAMPUAN KERJA TERHADAP KINERJA PEGAWAI DINAS SOSIAL DAERAH KABUPATEN TAPANULI SELATAN - Nelli Molida Harahap; Budi Krianto S.; Veronika Dumaria S.; Asikin Kesuma; Surya Gunawan (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2020)
The formulation in this research is how the influence of work discipline, organizational commitment and work ability to the performance of social service officers in the district of South Tapanuli, and the purpose of this research is to know and analyze The influence of work discipline, organizational commitment and work ability to the performance of social service employees of the District of South Tapanuli. This research is quantitative descriptive research. Data collection techniques are conducted through interviews, inquiry lists and documentation studies. The samples in this study were as many as 32 employees. Variables are measured at Likert scale. Hypothesis testing using multiple linear regression analyses through F-test and T-Test. results of the test in Unison indicate that the work discipline, organizational commitment and work ability have significant effect on the performance of officers in the social service office in the District of South Tapanuli regency with a value of Fcount 15,929 Ftable 2.90 and significance value of 0.000b. The Adjusted number of R Square is 0. 591 or (59.1%) Indicates that the percentage of contributions influenced by independent variables (work discipline, organizational commitment and work ability) on dependent variables (employee performance) of 59.1%. Partially, the work discipline significantly affects the performance of officers in the social service office of the District of South Tapanuli regency with a value of tcount ttable (3,990 2,037) and a significance value of 0. 000. The organizational commitment has a significant effect on the performance of employees at the social Service office of South Tapanuli regency with a value of tcount ttable (2,717 2,037) and significance value of 0. 011. Work capability significantly affects the employee 's performance in the social service office of the South Tapanuli district with a value of tcount ttable (3,135 2,037) and a significance value of 0. 004. The Highest value of a regression coefficient is a working discipline variable (X1) of 0. 494 or 43.0% and is the most dominant variable affecting employee performance in the social service office of South Tapanuli District